Thrombus formation during ECMO: Insights from a detailed histological analysis of thrombus composition. (3rd July 2022) - Staessens, Senna; Moussa, Mouhamed D.; Pierache, Adeline; Rauch, Antoine; Rousse, Natacha; Boulleaux, Eric; Ung, Alexandre; Desender, Linda; Pradines, Bénédicte; Vincentelli, André; Mercier, Olaf; Labreuche, Julien; et al.
Abstract: Objectives: Intra‐device thrombosis remains one of the most common complications during extracorporeal membrane oxygenation (ECMO). Despite anticoagulation, approximately 35% of patients develop thrombi in the membrane oxygenator, pump heads, or tubing. The aim of this study was to describe the molecular and cellular features of ECMO thrombi and to study the main drivers of thrombus formation at different sites in the ECMO circuits. Approach and Results: Thrombi ( n  = 85) were collected immediately after veno‐arterial‐(VA)‐ECMO circuit removal from 25 patients: 23 thrombi from the pump, 25 from the oxygenator, and 37 from the tubing. Quantitative histological analysis was performed for the amount of red blood cells (RBCs), platelets, fibrin, von Willebrand factor (VWF), leukocytes, and citrullinated histone H3 (H3Cit). ECMO thrombi consist of a heterogenous composition with fibrin and VWF being the major thrombus components. A clustering analysis of the four major histological parameters identified two typical thrombus types: RBC‐rich and RBC‐poor/fibrin‐rich thrombi with no significant differences in VWF and platelet content. Thrombus composition was not associated with the thrombus location, except for higher amounts of H3Cit that were found in pump and oxygenator thrombi compared to tubing samples. We observed higher blood leukocyte count and lactate dehydrogenase levels in patients with fibrin‐rich thrombi. Conclusion: We found that thrombus composition is heterogenous, independent of their location, consisting of two types: RBC‐rich and a fibrin‐rich types. We also found that NETs play a minor role. These findings are important to improve current anticoagulation strategies in ECMO.